Activity Antioxidant on Pigments of Bacterial Symbionts of Soft Coral From Jepara Sea - Masduqi, Ahmad Fuad; Franyoto, Yuvianto Dwi; Kusmita, Lia; Muchlisin, Sakti; Widyananto, Prasetyo Abi; Sulistyani, Sulistyani; Wijayanti, Diah Permata (Ma Chung Research Center for Photosynthetic Pigments, 2020)
Soft corals have been known to produce secondary metabolites, some of which may have anticancer, antifouling, antibacterial and antioxidants activity. It has been suggested that natural products from marine invertebrates have striking similarities to metabolites of their association microorganisms. Symbiont bacteria on soft coral can produce bioactive compounds that play an important role in chemical ecology and as a marine natural product. Marine bacteria associated with soft coral collected from Jepara were successfully isolated on medium ZoBell 2216E and screened to synthesize the pigment. This approach has allowed the use of this organism as an environmentally friendly alternative source of new natural pigment. This study found 25 bacterial isolates from 6 types of soft coral. Out of 25 bacterial isolates, only 3 bacterium, positively contains pigments. Four isolates, PCl 1, PS2 1, and PSa 2. Pigments analysis with UV spectrophotometric method showed the wavelength of pigments were in the range 300-600 nm. Genomic DNA was isolated from these colonies and nested PCR of the DNA was performed to amplify the 16S rDNA. Antioxidant activity was tested with the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. From the results of molecular identification by 16S rDNA method, it was shown that bacterium PCl 1, PS2 1, and PSa 2 was closely related to Pseudomonas stutzeri, Ponticoccus gilvus, Bacillus marisflavi with 99%, 99and 98% homology value. Antioxidant activity is as follows: PCl 1>PS2 1>PSA 2.